Gambaran Tingkat Produktivitas Kerja Karyawan Unit Pengemasan PT X Semarang - Nisa Trisna Natania (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Work productivity is a problem that needs to be considered by companies because it can affect the quality and quantity of the company in the face of competition and is the main key in achieving company goals. The purpose of this study is to determine the level of work productivity in employees of the packaging unit of PT X Semarang which is measured using six indicators of work productivity. This type of research is a descriptive analysis with a cross sectional  research design.The research sample was determined to be 188 packaging employees of PT X Semarang which was taken using purposive sampling. The instrument used is a structured questionnaire with data analysis carried out, namely a descriptive analysis test. The results of this study show that work productivity is in the good category as measured based on six work productivity indicators, including: ability indicators, indicators of improvement of achieved results, work morale indicators, self-development indicators, quality indicators, and efficiency indicators.